Amyloid Load: A More Sensitive Biomarker for Amyloid Imaging - Whittington, Alex (J Nucl Med, 2019)
Amyloid-β (Aβ) plays a key role in the pathogenesis of Alzheimer disease (AD) and can be imaged in vivo using (18)F-florbetapir PET. A composite SUV ratio (SUVr) is a commonly used outcome measure for quantifying the global Aβ burden; however, sensitivity is suboptimal and can lead to low power in clinical trials. We introduce amyloid load, Aβ(L), as a novel biomarker to quantify the global Aβ burden along with an automated algorithm for its calculation (Amyloid(IQ)). Aβ(L) is evaluated on cross-sectional and longitudinal data obtained from the Alzheimer’s Disease Neuroimaging Initiative. The cross-sectional data consisted of 769 subjects across the disease spectrum (211 healthy controls, 223 patients with early mild cognitive impairment, 204 with late mild cognitive impairment, and 132 with AD). The distributions of Aβ(L) in the 4 different classifications were compared, and the same analyses were applied to a composite SUVr outcome measure. The effect sizes (Hedges g) between all but one classification were higher for Aβ(L) than for composite SUVr, with the mean difference being 46%. Of the patients with early mild cognitive impairment, 147 had a 2-y follow-up scan, and the effect size between baseline and follow-up for Aβ(L) was 0.49, compared with 0.36 for a composite SUVr, demonstrating an equivalent increase in power for longitudinal data. These results offer evidence that Aβ(L) will be a valuable outcome measure in future Aβ imaging studies, providing a substantial increase in power over currently used SUVr methods.